Nocturnal Heart Rate and Cardiac Repolarization in Lowlanders With Chronic Obstructive Pulmonary Disease at High Altitude: Data From a Randomized, Placebo-Controlled Trial of Nocturnal Oxygen Therapy - Bisang, Maya; Latshang, Tsogyal D.; Aeschbacher, Sayaka S.; Huber, Fabienne; Flueck, Deborah; Lichtblau, Mona; Ulrich, Stefanie; Hasler, Elisabeth D.; Scheiwiller, Philipp M.; Ulrich, Silvia; Bloch, Konrad E.; Furian, Michael (Frontiers in Medicine, 2021)
Background Chronic obstructive pulmonary disease (COPD) is associated with cardiovascular disease. We investigated whether sleeping at altitude increases nocturnal heart rate (HR) and other markers of cardiovascular risk or arrhythmias in lowlanders with COPD and whether this can be prevented by nocturnal oxygen therapy (NOT). Methods 24 COPD-patients, median age 66y, FEV1 55% predicted, living <800m underwent sleep studies at Zurich (490m) and during 2 sojourns of 2 days each at St. Moritz (2’048m) sepa-rated by two-week-washout at <800m. During nights at 2’048m, patients received either NOT (2’048m-NOT) or ambient air (2’048m-placebo) 3l/min via nasal cannula according to a ran-domized, placebo-controlled cross-over trial. Sleep studies comprised ECG and pulse oximetry to measure HR, rhythm, HR-adjusted QT interval (QTc) and mean oxygen saturation (SpO2). Results In the first nights at 490m, 2’048m-placebo and 2’048m-NOT, medians (quartiles) of SpO2 were 92% (90;94), 86% (83;89), 97% (95; 98) and of HR were 73bpm (66;82), 82bpm (71;85) and 78bpm (67;74), (P<0.05 all respective comparisons). QTc increased from 417ms (404;439) at 490m to 426ms (405;440) at 2’048m-placebo (P< 0.05) and was 420ms (405;440) at 2’048m-NOT (P=NS vs. 2´048m-placebo). The number of extrabeats and complex arrhythmi-as was similar in all conditions. Conclusions While staying at 2’048m lowlanders with COPD experienced nocturnal hypoxemia in association with an increased HR and prolongation of the QTc interval. Nocturnal oxygen therapy significantly improved SpO2 and lowered HR, without changing QTc. Whether oxygen therapy would reduce heart rate and arrhythmia during longer altitude sojourns remains to be elucidated.